Perancangan Sistem Kendali Robot Tangan Menggunakan Motor Servo Dan Sensor Flex Berbasis Mikrokontroler Atmega32 - Sambodo, Pujo (2016)
Technological developments, particularly the field of robotics is currently growing very rapidly seen from the many application of robotics technology based control systems and artificial intelligence in the fields of industry, education, and everyday life. Research and development of various kinds of robots from time to time continue to improve the effectiveness, productivity and employment among various automation robot manipulator such as a robot arm (robotic arm). This study used a flex sensor that is placed on the glove to detect the position of the finger more easily and simply. Flex sensors have output (output) in the form of resistance that is processed by the microcontroller as data to the servo motors for motion commands in the form of pulses of PWM (Pulse Width Modulation). LCD device / liquid crystal display shows the value of the input data (input) sensor flex. One can directly determine the movement of the robot arm directly corresponding movements of the operator. Robot hand made tested have tried and succeeded gripping round and square-shaped goods with varying size and weight, such as ping-pong balls and ball kastik respectively 40.5 and 61.5 mm in diameter, 175ml bottles of body fragrances, and phone 128, 7 grams.